Physiological adaptations and analysis of training content in high school cross-country runners - Loprinzi, P. D.; Brodowicz, G. R. (Research in Sports Medicine, 2008)
The purposes of this study were to examine effects of a season of training on aerobic performance in cross-country distance runners and to analyze the training using subjective and objective techniques. Subjects averaged 184 minutes of running per week, with 45%, 24%, and 31% occurring in zones below, near, and above the heart rate (HR) corresponding to ventilatory threshold (VTHR), respectively (Zone 1: HR > 15 bpm below VTHR; Zone 2: HR between Zone 1 and VTHR; Zone 3: HR > VTHR). Maximal oxygen uptake (O2max) increased by 5.1%, 5-km race time by 46 seconds (3.7%), and 2-km time trial performance by 54 seconds (10.7%) from pre- to postseason. Results are similar to previous research demonstrating that short-term (< 3 months) endurance training elicits improvements in various physiological parameters. Findings were not consistent with previous research that suggests a discrepancy may exist between the runners' perceptions and the physiological effects of their training.